Od Turgieniewa do Moore’a — rola literatury rosyjskiej w ideologii Ligi Gaelickiej - Jarząb, Joanna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The paper scrutinizes George Moore’s fascination with Ivan Turgenev’s literary output, which led the Irish novelist into writing his first collection of short stories. Interestingly, the abundance of influences resulted in George Moore being one of the few Irish writers, who, throughout his writing career, went from the state of eager interest in the Celtic Revival to the bitter criticism of the Gaelic League, visible in his autobiographical accounts. Interestingly, his collection of short stories The Untilled field (1903) well illustrates this process. Initially written in order to be used by the members of the Gaelic League as a text for translation into Irish, and therefore as a medium of dissemination of the native language among Irish people, later became a source of influence for James Joyce’s Dubliners. Therefore, the following paper aims to investigate the case of George Moore’s The Untilled field as a literary and cultural phenomenon. The reference to Ivan Turgenev’s A sportsman’s sketches (1852) is to be scrutinized. What is more, the paper investigates how the initial interest in the idea of a „Dublin Turgenev” did not end on this particular project but had a greater impact on Moore’s literary career.